Em direção a produção de conhecimento modo 2: análise e proposição de um framework para pesquisa em processos de negócios - Veit, Douglas Rafael (Universidade do Vale do Rio dos Sinos, 2013)
The research on business processes has been developed around a production of disciplinary knowledge, traditionally known as Mode 1 of knowledge production. The studied problems are solved with this approach in a context in which academic knowledge prevails, with no major concerns about the practical applicability of the knowledge generated. Thus, this dissertation aims to take the first step towards Mode 2 knowledge production, proposing a framework for the production of this type of knowledge in the development of research in business processes. For this, was conducted a qualitative and quantitative literature search for conceptualize and define classes of problems through multidisciplinary evaluation of the last 5 years (2007-2012) in publications of Business Process Management Journals. The objectives of this study were achieved with the construction of this framework, where classes of problems have been launched and presented to show the way for a future research agenda in business processes.
Keywords: Produção do conhecimento; Modo 2; Classes de problemas; Processos de negócios; Pesquisa bibliográfica; Knowledge production; Mode 2; Problem classes; Business processes; Bibliographic research; ACCNPQ::Engenharias::Engenharia de Produção